Leveraging patient‐reported outcomes (PROs) in patients with pancreatic cancer: The Pancreatic Cancer Action Network (PanCAN) online patient registry experience. (3rd September 2021) - Gupta, Arjun; Khalid, Omar; Moravek, Cassadie; Lamkin, Anica; Matrisian, Lynn M.; Doss, Sudheer; Denlinger, Crystal S.; Coveler, Andrew L.; Weekes, Colin D.; Roeland, Eric J.; Hendifar, Andrew E.; Nipp, Ryan D.
Abstract: Background: The Pancreatic Cancer Action Network (PanCAN) Patient Registry is an online, pancreatic cancer‐specific, global registry enabling patients to self‐report sociodemographics, disease/management characteristics, and patient‐reported outcomes (PROs). We sought to describe the creation, user experience, and research potential of the PanCAN Registry. Methods: We obtained data to describe (1) the creation of the Registry (questionnaire development, marketing efforts, and regulatory considerations); (2) the user experience (user characteristics and interactions with the registry following inception); and (3) the research potential of the registry (comparing PROs and treatment patterns by age [±65 years] and treatment site [community or academic] for users with de novo metastatic disease). Results: The Registry was conceived as part of PanCAN's strategic plan for a personalized therapy initiative. PanCAN staff and disease expert consultants developed questionnaires hosted on an electronic PRO platform. Users had the option to include their data in research efforts, and the Registry platform received institutional review board approval. From 7/2015 to 12/2020, 2187 patients visited the registry and 1697 (77.6%) completed at least one survey (median age = 64 years [range: 24–90], 47.9% women, 88.7% White, 34.0% metastatic disease). Among patients with metastatic disease ( N  = 567), 46.0% were ≥65 years old and 67.5% received treatment at community sites. Patients ≥65 years reported feeling less hopeful about the treatment plan (12.4% vs. 24.3%, p  = 0.003), and patients treated at community sites reported more frequent treatment breaks of >2 weeks (58.2% vs. 28.1%, p  < 0.001). Conclusions: Our findings demonstrate the feasibility, usability, and research potential of an online PRO registry for patients with cancer. This description of the PanCAN Registry should inform future registry‐building efforts to facilitate standardized PRO reporting and provide a valuable research database. Clinical trial registration number: Not applicable. Abstract : The Pancreatic Cancer Action Network (PanCAN) Patient Registry is a voluntary, global, pancreatic cancer‐specific registry enabling patients to self‐report sociodemographics, disease/ management characteristics, and patient‐reported outcomes. In this manuscript, based on over 2000 patients visiting the PanCAN Registry over a 5‐year period, we describe its creation, user experience, and research potential, which can guide future registry building efforts (including standardized patient‐reported outcomes collection).